The Effect of Advanced Maternal Age on Embryo Morphokinetics - Warshaviak, Miriam; Kalma, Yael; Carmon, Ariela; Samara, Nivin; Dviri, Michal; Azem, Foad; Ben-Yosef, Dalit (Frontiers in Endocrinology, 2019)
Purpose: To compare the morphokinetic parameters of pre-implantation development between embryos of women of advanced maternal age (AMA) and young women. Methods: Time-lapse microscopy was used to compare morphokinetic variables between 495 embryos of AMA women ≥ age 42 years and 653 embryos of young patients (<age 38 years) who underwent IVF in our unit. Developmental events annotated and analyzed include observed cell divisions in correlation to the timing of fertilization, synchrony of the second (s2) and third cell cycles (s3) and the duration to the second (cc2) and third cleavages (cc3). Results: No significant differences were observed in cleavage times between the embryos of AMA and the control embryos. Interestingly, the older embryos appear to be more prone to developmental arrest (a higher percentage of embryos of older women arrested at 4–7 cells resulting in less embryos reaching the 8-cell stage (66% vs. 72%, respectively), though this difference did not reach a significance at least during the first 3 days of development (p > 0.05). Conclusions: While early morphokinetic parameters do not reflect dynamics unique to embryos of older women, a tendency toward developmental arrest was observed, which would likely be even more pronounced at later stages of development.